2011
DOI: 10.1103/physreva.84.012311
|View full text |Cite
|
Sign up to set email alerts
|

Informational derivation of quantum theory

Abstract: We derive Quantum Theory from purely informational principles. Five elementary axiomscausality, perfect distinguishability, ideal compression, local distinguishability, and pure conditioning-define a broad class of theories of information-processing that can be regarded as standard. One postulate-purification-singles out quantum theory within this class.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
923
1
7

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 554 publications
(940 citation statements)
references
References 35 publications
9
923
1
7
Order By: Relevance
“…4 We can also consider mixtures of two or more mixed states. If M 1 and M 2 are two subspaces of V associated with two states, then M 1 ∨ M 2 is the subspace associated with a mixture of the two.…”
Section: Mixed States In Mqtmentioning
confidence: 99%
See 1 more Smart Citation
“…4 We can also consider mixtures of two or more mixed states. If M 1 and M 2 are two subspaces of V associated with two states, then M 1 ∨ M 2 is the subspace associated with a mixture of the two.…”
Section: Mixed States In Mqtmentioning
confidence: 99%
“…The most celebrated example of this approach was Bell's analysis [2], which showed that entangled quantum systems have statistical properties unlike any hypothetical local hidden variable model. More recently, there have been several efforts to give quantum theory an operational axiomatic foundation [3,4,5]. In these efforts, a general abstract framework is posited to describe system preparations, choices of measurement, observed results of measurement, and probabilities.…”
mentioning
confidence: 99%
“…In the recent past, there have been several attempts to derive (finite-dimensional) quantum theory within a framework of probabilistic theories 12,28,29 . The idea is the following.…”
Section: Article Nature Communicationsmentioning
confidence: 99%
“…In fact, there actually exist a number of successful reconstructions of finite dimensional quantum theory from operational axioms, most of which have been performed within the frameworks of generalized or operational probability theories [9,[23][24][25][26][27][28][29][30][31][32] (see also [33] which is adapted to a space-time language and the more mathematical reconstructions [34,35]). Despite the beauty and great technical achievements of some of these reconstructions, they arguably come short of providing a fully satisfactory physical and conceptual picture of quantum theory.…”
Section: Introductionmentioning
confidence: 99%